KAJIAN EFEKTIVITAS EKSTRAK GEL IKAN TOMAN (Channa micropeltes) PADA LUKA BAKAR MENCIT (Mus musculus) - Firlianty Firlianty; Hermansyah Hermansyah; Windarina Samosir (Universitas Lambung Mangkurat, 2019)
This study aims to determine the study of the effectiveness of toman fish (Channa micropeltes) gel extract on healing burns of mice (Mus musculus). This research was conducted for 4 months, starting from September 2018 to January 2019. This study used the experimental method and data analysis using a completely randomized design with 4 children and three replications: treatment A as control, treatment B giving toman fish extract gel (Channa micropeltes ) 1.5%, treatment C 3% and treatment D 4.5%. The results showed that on day 4, day 8 and day 12 showed that the administration of gel extract had a significant effect on changes in the length of burns of mice (Mus musculus) (P>0.05). In vivo test results on male mice with toman fish gel extract can capture the healing of burns in mice.